Enhancing Nutritional Status in Children with Cerebral Palsy: The Impact of Parental Feeding Rules Counseling and Special Spoon Utilization - Mansur, Arif; Sulistyawati, Nining; Sari, Ira Mulya (Indonesian Journal of Disability Studies, 2023)
The objective of this article is to evaluate the effect on Parental Feeding Rules Counseling and Utilization of Special Spoons on the Nutritional Status for children with cerebral palsy. Children with cerebral palsy (CP) experience nutritional deficiencies resulting from food intake challenges caused by brain and nervous impairments. However, parental implementation, such as counseling on feeding rules and the use of specialized spoons, needs to be improved.  Method: A Pre Experimental design with a One Group Pretest-Posttest approach, namely counseling on feeding rules and the utilization of specialized spoons, on the food intake and nutritional status of children with cerebral palsy. The research was conducted at Griya Lare Utami and Special Need Schools  1 Bantul, with a minimum sample size of 18 parent-child pairs with cerebral palsy, selected through purposive sampling. Data analysis was performed using bivariate analysis with the Paired t-test. Result: Child weight and Stature have increase. Conclusion: The intervention programme seemed to increase in the weight and stature indicator, but there has been no change in the nutritional status of BMI-for-age and  Length-for-age.